Bispectral Index in Poisoning Cases with Multi-drug Ingestion: A Predictable Role for Early Endotracheal Intubation - Eizadi-Mood, Nastaran (J Res Pharm Pract, 2018)
OBJECTIVE: Bispectral index (BIS) is one of the several methods used to monitor the depth of anesthesia. Poisoning with ingestion of different drugs is one of the most common poisonings that have different clinical signs from drowsiness to coma. This study was performed to compare the BIS index number in poisoned patients with multi drugs ingestion with or without the need for endotracheal intubation. METHODS: This cross-sectional study was performed on poisoned patients with ingestion of different drugs referring to Clinical Toxicology Department of Noor University Hospital, Isfahan, Iran. The clinical signs and symptoms and the vital signs at the admission time were measured, and the required therapies were given. The endotracheal intubation was done for patients who had the indication of intubation. BIS was monitored and compared for all patients with or without a need for intubation on the admission time and time of endotracheal intubation. Obtained data were analyzed by SPSS software. FINDINGS: At the admission time, the mean (standard error [SE]) BIS index value for poisoned patients who needed endotracheal intubation was 66.47 ± 2.57 in comparison with 85.21 ± 1.47 for patients who did not need intubation (P < 0.001). The results of receiver operating characteristic curve (mean ± SE) showed the discrimination was excellent for BIS (0.899 ± 0.04; 95% confidence interval: 0.81–0.98) (P < 0.0001). BIS <79.5 had the sensitivity 88% and specificity 87% for endotracheal intubation. CONCLUSION: BIS is an appropriate index for prediction of the need to intubation in poisoned patients with ingestion of different drugs.